Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The role of interactive radio instruction in the coronavirus (COVID-19) education response - McBurnie, Chris (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Every week that passes we see the number of classrooms closed due to COVID-19 increase. During these unprecedented times, the Hub’s mission — to increase the use of evidence-based decisions around EdTech — is more important than ever. We must make sure learning goes on. […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The Role of Interactive Radio Instruction in the COVID-19 Education Response - McBurnie, Chris (Open Development & Education, 2020)
Reading Time: 3 minutes At a time when the COVID-19 pandemic has forced over 1.5 billion students out of school, governments in resource-constrained countries have looked to interactive radio instruction (IRI) to ensure educational continuity. In the past week, we spoke with the Rising Academy Network to consider what an IRI programme could look like and why policymakers have […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found